Concept of SARS-CoV-2 Vaccine Design to Fight COVID-19 Pandemic: A Review Insight (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cluster of pneumonia infection emerged in Wuhan, China due to severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2). Additionally, more than 190 countries have confirmed 82 million casesof SARS-CoV-2 infection. Currently, there is a SARS-CoV-2 epidemic, and no effective prophylacticmethods are available. A vaccine is considered as an effective method to restrict an epidemic. Severalvaccine designing techniques have been established, which is enabling researchers from various institutesfor developing vaccine towards SARS-CoV-2 infections. In this review, we condense the development ofvaccine research against SARS-CoV-2.
Keywords: COVID-19, SARS-CoV-2, Vaccine Design.